Community development and its influence on community policing - Sulaiman, Abdul Hadi; Othman, Jamilah; Hamsan, Hanina Halimatussaadiah; Abu Samah, Bahaman; D’Silva, Jeffrey Lawrence (Science Publications, 2012)
Problem statement: Undeniably communities around the world are facing numerous challenges in the development process and one of it is to ensure a safe community. To achieve this, community policing is deemed important as an important mechanism that will ensure safety and a free-crime society. The main purpose of this study is to seek the interrelationships between the various approaches in community development and how it can be embedded in community policing. Approach: This study used the existing literature and other relevant documents to seek for the implementation of community policing in Malaysia. Results: The outcome of the study showed that community policing is alive in Malaysia and most communities accept the good cooperation between the police and community in reducing crime. Conclusion: This study showed that more efforts need to be taken to further strengthen collaborative ties between the police and the community as it is evident that such collaboration will help to enhance the well-being of society.